Faktor-Faktor yang Mempengaruhi Penduduk Miskin di Sulawesi Tengah - Agus Tri Basuki; Roan Ramadhan Koem (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the factors that influence the number of poor people in districts/cities in Central Sulawesi Province. This study uses a panel data regression approach. Panel data is a combination of time series data and cross section data. The data used in this study came from Central Sulawesi BPS from 2017 to 2021. The results showed that GRDP and the Poverty Line had a significant effect on the Number of Poor Population in Regencies/Cities in Central Sulawesi Province. Meanwhile, the number of unemployed and government spending in the education sector is not significant to the number of district/city poverty in Central Sulawesi Province.Â